STRUKTUR PENDAPATAN RUMAH TANGGA PETANI PADI SAWAH SKALA KECIL DI KELURAHAN BINUANG KAMPUNG DALAM KECAMATAN PAUH KOTA PADANG - Alin Deri Utama (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Impairment Basic Farmer or agricultural production, especially paddy and scalefarming with small land holding farmers' income resulted primarily from commodity paddyrice into decline and insufficient to meet the needs of the family. Thus the farmerhouseholds will seek other than rice commodity businesses or businesses from outside theagricultural sector to supplement household income. This is the main focus of this study.The research was conducted in the Village Binuang Kampung Padang Pauh InDistrict of which is sub urban or suburban. This study is a survey research method used isdescriptive quantitative. Respondents in this study were farmers with an area of 0.5 haland holding down. The results showed that the analysis of the results of the calculationsshowed that farming paddy crop production is still far from enough and have not been ableto meet the needs of farm households.Where the average penghasilan farmers fromfarming rice per month ranging from Rp 200,000, - up to Rp 1.800.000, -. Thereforefarmers in the study area are looking for alternative business venture beyond rice crops tosupplement household income.In terms of the age dependency ratio is known that respondents with lowpopulation dependency ratio even more to make efforts to increase household incomeapart from paddy farming activities. Meanwhile, if viewed from the aspect of land densitylevel to the highest percentage of respondents who do all of the activities or businesses arehousehold respondent farmers with land density levels are relatively small and the numberof family members that much.Keywords: Household Income Structure Farmer, Rice, Non Agricultural Sector